Assessing the Operational Effectiveness of the Intelligence Cycle Within the Philippine Army Towards Insurgency - Sangil, Lester E.; Lecodine, Jay-Ar V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study aimed to evaluate the effectiveness of the intelligence cycle within the Philippine Army and identify associated risks and flaws. Specifically, it sought to determine the components of the intelligence cycle used by the Philippine Army such planning and programming, execution, and review and assessment. Moreover, it also determined the extent of effectiveness of these intelligence cycle components, the weaknesses and operational risks are associated with the current Intelligence Cycle Process, potentially compromising its effectiveness in gathering accurate and timely intelligence, and strategies and measures can be proposed to enhance the effectiveness and resilience of the Intelligence Cycle. It employed descriptive research design and employ survey questionnaires with a 5-point Likert scale. The study was conducted in the Area of responsibility of 7th Infantry Division, randomly selected 80 intelligence personnel from various ranks and roles. Data collection was methodical, ensuring validity and reliability through expert validation and pilot testing. In addition, it employed descriptive statistics and run through SPSS. The findings revealed that the Philippine Army strongly integrates intelligence findings into its planning, execution, and assessment phases, with high levels of agreement found in areas such as intelligence-driven mission planning (mean = 3.90), monitoring and adjusting operations based on real-time intelligence (mean = 3.99), and systematic review processes for intelligence operations (mean = 3.91), highlighting the Army's robust application of the intelligence cycle. The intelligence cycle components were rated as very effective in all phases, with planning (mean = 3.97), execution (mean = 3.97), and review and assessment (mean = 3.97) all receiving high ratings. These findings demonstrate that intelligence-driven planning and operations significantly enhance operational goals and mission success. However, weaknesses were identified, including a lack of specialized personnel (mean = 3.84), inconsistent intelligence analysis methodologies (mean = 3.08), and weak inter-unit intelligence sharing (mean = 3.09). Operational risks such as limited funding (mean = 3.90), logistical constraints (mean = 3.38), and poor coordination with other agencies (mean = 3.78) were also noted, which compromise the cycle's effectiveness. To address these challenges, strategies such as modernizing training, improving resource mobilization, and establishing a feedback mechanism for knowledge sharing were proposed. These measures aim to improve the intelligence cycle's effectiveness, with expected outcomes including better readiness through specialized training, improved mission success via coordinated deployment, and enhanced resource availability through partnerships. The research found that the Philippine Army effectively incorporates intelligence into planning and execution, improving unit readiness, flexibility, and mission performance. The intelligence loop improves planning, resource allocation, and operational execution, and real-time updates help units exploit threats and opportunities. The cycle's precision and reactivity are limited by resource constraints such inadequate workers, equipment, and funds. To improve the intelligence cycle's efficacy and resilience, invest in training, tools, infrastructure, feedback loops, and coordination.